Evolution of stress and morphology in thermal barrier coatings - Wang, Xin; Atkinson, Alan; Chirivi, Laura; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2010)
Residual stress in the thermally grown oxide (TGO) in thermal barrier coatings (TBCs) was measured by photoluminescence piezospectroscopy (PLPS) and stress maps created to track local stress changes as a function of thermal cycling. The local stress images were observed to be correlated with morphological features on the metal surface that were purposely introduced during specimen preparation. Local stress relaxation and morphological evolution with thermal cycling were studied using the stress maps combined by post-mortem SEM examination. It was found that the morphology in the specimen having an initial polished surface was quite stable, while that in the specimen with a rough surface was unstable. The average residual stress in the specimen with the unstable morphology decreased with thermal cycling and it eventually failed along TGO/YSZ interface. The specimen with stable morphology maintained a high TGO stress throughout the thermal cycling process and failed along TGO/bond coat interface. The rough surface was also found to give rise to the formation of transition alumina (theta-Al2O3) in the TGO which was correlated with a reduced TGO stress. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: TBCs Stress mapping Luminescence spectroscopy Interface morphology Failure mechanism grown oxide stress bond coat photoluminescence piezospectroscopy cyclic oxidation residual-stress luminescence temperature durability behavior failure